IoT Based Waste Management System for Smart Cities - Patil, A; Prajapati, S; Salunke, R; Chaudhari, SS (International Journal of Computer Sciences and Engineering, 2025)
In present day scenario, many times we see that the garbage bins placed at various public places in cities are over ﬂowing due to increase in the waste every day. It creates unhygienic condition for the people and creates bad odour around the surroundings thus leads in spreading some deadly diseases and human illness. To avoid such situation, we are planning to design “IoT based Waste Management System for Smart Cities”. In this proposed system, there will be multiple garbage bins located throughout the city or campus, these garbage bins will be equipped with low cost embedded device which will helps in tracking the level of garbage in particular bin along with location tracking module to get real time location of bin. All the real time information including garbage level as well as location of that bin will be send frequently to concern authority and garbage collector truck driver as well. The truck driver will have android application which will show real time information about all bins to driver that which bin is how much full and which location in graphical form. So he can go directly to place where actually need to empty the garbage bin to achieve Resource optimization, cost reduction, time management and active participation of truck driver.